Delegitimasi Putusan Mahkamah Konstitusi Nomor 114/PUU-XXIII/2025 Melalui Peraturan Kepolisian Nomor 10 Tahun 2025 dalam Prinsip Supremasi Konstitusi - Baihaqi Samudera Sastra (Equality : Jurnal Hukum dan Keadilan, 2026)
The issuance of Police Regulation Number 10 of 2025 has generated considerable controversy due to its alleged inconsistency with Constitutional Court Decision Number 114/PUU-XXIII/2025, which removed the phrase “or not based on an assignment from the Chief of the Indonesian National Police” from the Elucidation of Article 28 paragraph (3) of Law Number 2 of 2002 concerning the Indonesian National Police. This inconsistency is manifested in Article 3 paragraph (2) of Police Regulation Number 10 of 2025, which explicitly designates seventeen ministries and government agencies that may be occupied by active police officers without requiring their resignation or retirement from police service. Such inconsistency not only constitutes a violation of the final and binding nature of Constitutional Court decisions but also potentially infringes upon citizens’ constitutional rights to legal certainty and equal treatment before the law, as guaranteed by the 1945 Constitution of the Republic of Indonesia. This study aims to constitutionally examine the conformity of Police Regulation Number 10 of 2025 with the aforementioned Constitutional Court decision, as well as to formulate an ideal model for drafting police regulations within the framework of constitutional supremacy. This research employs a normative legal method using statutory, case, and conceptual approaches. The findings indicate that Police Regulation Number 10 of 2025 is not aligned with Constitutional Court Decision Number 114/PUU-XXIII/2025 and the principle of constitutional supremacy upheld in Indonesia. The issuance of this regulation is also considered inconsistent with the police reform agenda aimed at improving governance within the Indonesian National Police. This study emphasizes that the ideal practice of drafting implementing regulations requires strict compliance with and reference to Constitutional Court decisions, while positioning the Constitution as the primary normative foundation to strengthen the implementation of constitutional supremacy within Indonesia’s constitutional system.